Penerapan Lean Tools Change Acceleration Process (CAP) Model dan Spaghetti Diagram Pada Proses Produksi Sofa di PT. XYZ - Barus, Wan Habibi Rahman; Sriwana, Iphov Kumala (Universitas Al Azhar Indonesia, 2023)
PT. XYZ is a company engaged in the furniture manufacturing, one of which is sofa. PT. XYZ as a large company has a vision towards waste elimination and the application of lean tools to improve effectiveness and efficiency in its supply chain. This vision is difficult to realise due to the lack of socialization, inavailability of company skills/expertise, and the absence of guidance for employees in implementing the lean SCM concept. The purpose of this study is to identify the formulation of stages in change management using the Change Acceleration Process (CAP) model. The spaghetti diagram approach is carried out to measure the distance between materials/materials and workers and an analysis is carried out to improve the layout of the work station to reduce the movement distance. Improvements to the layout of the work station using the Activity Relationship Chart and continued with the Activity Relationship Diagram. From the results of the improvement in the layout of the work station, the initial displacement distance of 174m was shortened to be only 116.4m.Keywords - Lean SCM, Change Acceleration Process, Spaghetti Diagram, Activity Relationship Chart, Activity Relationship Diagram